Exploring potentially synthetic genes related to diarrhetic shellfish toxins production in Prorocentrum sp. via comparative transcriptomics - Danlin Zheng; Jingyi Cen; Peiliang Chen; Ligong Zou; Jian Zou; Qun Li; Songhui Lu (Ecotoxicology and Environmental Safety)
Harmful algal blooms (HABs), exacerbated by climate change and environmental disturbances, pose global challenges due to marine toxin contamination, particularly diarrhetic shellfish toxins (DSTs). DSTs are prevalent marine toxins, and understanding their synthesis is vital for managing fisheries and mitigating environmental triggers. This study delves into the synthesis mechanisms of DSTs in Prorocentrum arenarium and Prorocentrum lima, which vary in toxin types and concentrations. We conducted a comprehensive comparative transcriptomic analysis to identify potential toxin-related genes, focusing on polyketide synthases (PKSs) and fatty acid synthases (FASs). Our research predicted 96 PKSs and 91 FASs genes, with a detailed examination of their sequences to elucidate dinophysistoxins (DTXs) synthesis. Additionally, we analyzed differential gene expression of PKSs in P. arenarium under nitrogen and phosphorus-limited conditions, revealing a correlation between specific PKSs gene expression patterns and okadaic acid (OA) content variations. These findings suggest a potential role of the fatty acid biosynthesis pathway in DSTs synthesis. While not completely uncovering the biosynthetic pathway of DSTs, our study offers crucial insights and genomic resources for future research on dinoflagellate toxin production mechanisms.